KEEFEKTIFAN EKSTRAK TEPUNG DAUN MIMBA (Azadirachta indica A. JUSS) DENGAN PENAMBAHAN BEBERAPA JENIS SURFAKTAN TERHADAP ULAT GRAYAK (Spodoptera litura FAB.) PADA TANAMAN KEDELAI (Glycine max L. MERRILL) - Eunike JH Sidauruk; Hafiz Fauzana; Desita Salbiah (DINAMIKA PERTANIAN, 2017)
Neem leaves powder extract is a bioinsecticide which can be used to control the pest. The active compound of neem leaves powder extract is easy to be disentangled by the ultraviolet, so that the effectiveness of application itis low in the field. The alternative to solve this problem can be used the addition surfactant to the neem leaves powder extract. The purpose of this research was to determine the influence and the kind of surfactant which is best to increase the effectiveness of neem leaves powder extract to Spodoptera litura pest on a soybean plant. The research was using a completely randomized design (CRD) with four treatments and five replications so there were 20 unit experiments. The treatment has used some kind of surfactant with the different active compound; linear alkylbenzene sulphonate (LAS), alkyl poly glycol ether (APE), alkylphenol ethoxylate (AE) and polyoxyethylene sorbitan monolaurate (PSM). The results showed the addition of synthetic surfactant with the active compound APE, AE and PSM can increase the effectiveness of neem leave powder extract80 g/lof water to the early death, lethal time 50 and total mortality of S. litura. The intensity attack of S. litura showed APE tends to be better to increase the effectivity of neem leaves powder extract than AE and PSM.